Palladium‐Catalyzed Allylic Arylation of Allylic Ethers with Arylboronic Acids Using Hydrazone Ligands. Issue 8 (29th January 2013) - Mino, Takashi; Kogure, Taketo; Abe, Taichi; Koizumi, Tomoko; Fujita, Tsutomu; Sakamoto, Masami
Abstract: Unsymmetrical 1, 3‐diarylpropenes were synthesized in good to high yields by the palladium‐catalyzed allylic arylation of allylic ethers, such as a cinnamyl phenyl ether, with a variety of arylboronic acids using a hydrazone1a –Pd(OAc)2 system in DMAc/H2 O. Using this catalyst, eugenol was also synthesized from allyl phenyl ether with (4‐hydroxy‐3‐methoxyphenyl)boronic acid pinacol ester. Abstract : A palladium‐catalyzed allylic arylation of cinnamyl phenyl ether derivatives with a variety of arylboronic acids using 5 mol‐% of a hydrazone1a –Pd(OAc)2 system in DMAc/H2 O at 50 °C gave 1, 3‐diarylpropenes in good yields. We also succeeded with the synthesis of eugenol by a palladium‐catalyzed allylic arylation.